2019
DOI: 10.1097/mlr.0000000000001063
|View full text |Cite
|
Sign up to set email alerts
|

Missing Data in Marginal Structural Models

Abstract: Background: The use of marginal structural models (MSMs) to adjust for time-varying confounding has increased in epidemiologic studies. However, in the setting of MSMs, recommendations for how best to handle missing data are contradictory. We present a plasmode simulation study to compare the validity and precision of MSMs estimates using complete case analysis (CC), multiple imputation (MI), and inverse probability weighting (IPW) in the presence of missing data on time-independent and time-varying confounder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Second, this article addresses missing data in both outcomes and confounders. Previous studies addressing missing data in time‐varying settings have focused on missingness in the confounders 10‐13 . As with our study, those studies suggested that both IPW and MI provide minimal biases in estimating time‐varying treatment effects.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Second, this article addresses missing data in both outcomes and confounders. Previous studies addressing missing data in time‐varying settings have focused on missingness in the confounders 10‐13 . As with our study, those studies suggested that both IPW and MI provide minimal biases in estimating time‐varying treatment effects.…”
Section: Discussionsupporting
confidence: 79%
“…CER studies that use longitudinal, observational data are likely to be affected by time‐varying confounding and missing data 10‐13 . Appropriately addressing these two major issues is a necessary step for obtaining unbiased ATE estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, an appropriate OGM has to be applied to generate outcomes based on the resampled covariates. 5,7,[25][26][27][28][29][30][31][32][33][34] Statistical plasmodes have often been utilized in causal (propensity-based) methods using weighted regression models. The application of these weighted regression models is often related to the presence of a complex covariance structure.…”
Section: Plasmode Data Simulationmentioning
confidence: 99%
“…The SimDesign Package (Chalmers & Adkins, 2020) and the related MonteCarlo Package (Leschinski, 2019) follow a similar line of thought but focus on easy replication of the analyses and providing summaries of simulated data. simstudy has been used in a variety of fields for theoretical exploration of research methodology (Anderson, Wennberg, & McMullen, 2019;El Alili et al, 2020;Kirasich, Smith, & Sadler, 2018;Krzykalla, Benner, & Kopp-Schneider, 2020;Liu, Chrysanthopoulou, Chang, Hunnicutt, & Lapane, 2019;Nickodem, 2020;Thoya, Waititu, Magheto, & Ngunyi, 2018;Wang & Ma, 2020), power calculation for trials (Wei et al, 2019) and other simulation tasks supporting researchers (Chukwu, 2019;Forthun et al, 2020;Horry, Fitzgerald, & Mansour, 2020;Renson, Schubert, & Bjurlin, 2017).…”
Section: Statement Of Needmentioning
confidence: 99%